Islam and social change in French West Africa: history of an emancipatory community - Hanretta, Sean (African studies, 2009)
Exploring the history and religious community of a group of Muslim Sufi mystics in colonial French West Africa, this study shows the relationship between religious, social and economic change in the region. It highlights the role that intellectuals played in shaping social and cultural change and illuminates the specific religious ideas and political contexts that gave their efforts meaning. In contrast to depictions that emphasize the importance of international networks and anti-modern reaction in twentieth-century Islamic reform, this book claims that, in West Africa, such movements were driven by local forces and constituted only the most recent round in a set of centuries-old debates about the best way for pious people to confront social injustice. It argues that traditional historical methods prevent an appreciation of Muslim intellectual history in Africa by misunderstanding the nature of information gathering during colonial rule and misconstruing the relationship between documents and oral history.